Impact and recoverability of metals from waste: a case study on bottom ash from municipal solid waste incineration plants - Ghani, Junaid; Toller, Simone; Dinelli, Enrico; Funari, Valerio (Frontiers in Environmental Science, 2023)
Municipal Solid Waste Incineration (MSWI) plants generate significant amounts of solid end-products such as bottom ash (BA) containing potentially toxic elements like Cr, Ni, As, Cd, and Pb, base elements (e.g., Si, Al, Fe, Ti, Cu, and Zn), and other valuable technology-critical elements (TCE) such as Co, Ga, Mg, Nb, P, Sb, Sc, V, Li, Sr, and REE. The accurate determination of these elements in anthropogenic wastes and the assessment of their removals are crucial for the circular economy. This paper aims to characterize BA samples from two Italian MSWI plants (named FE and FC) by X-Ray Fluorescence (XRF) and comparatively assess the removal of a selection of elements after aqua regia digestion (ARD) method followed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analytical determination. According to the XRF analysis, Ca, Fe, Al, Mg, and Na had high concentrations in BA and their contents increased with decreasing particle size in both FE and FC samples. The Enrichment Factor (EF) based on upper continental crust’s average values, of Zn, Cu, and Pb was high (EF >30), while Cr, Ni, and As were scarcely enriched (EF >1) whereas REE enrichment was very low (EF <1). In both FE and FC plants, the Degree of Elements Extractability (DE) was high (> 80%), especially in the fine-grained fractions of MSWI bottom ashes. The Enrichment Factor (EF) based on upper continental crust average values, of Zn, Cu, and Pb was high (EF >30) and Cr, Ni, and As were scarcely enriched (EF >1) whereas REE enrichment was very low (EF <1). The bibliometric analysis helped highlighting research trends in the assessment and treatment of MSWI-BA, discriminating the literature impact on environment/health issues and recovery/recycling strategies for the circular economy associated to the MSWI-BA material. Although higher data coverage is needed, the present study suggests ARD as an effective method for better understanding the environmental impact and recoverability of useful elements from anthropogenic materials like MSWI bottom ashes.